An overview of organosulfur compounds from Allium spp.: From processing and preservation to evaluation of their bioavailability, antimicrobial, and anti-inflammatory properties. (15th March 2019) - Putnik, Predrag; Gabrić, Domagoj; Roohinejad, Shahin; Barba, Francisco J.; Granato, Daniel; Mallikarjunan, Kumar; Lorenzo, José M.; Bursać Kovačević, Danijela
Highlights: Organosulfur and other bioactive compounds of Allium spp. are thermally unstable. Conventional processing tends to decrease nutritional value and bioactivity. Innovative processing is useful to preserve target compounds from Allium genus. Abstract: The use of Allium species and their extracts has been known since immemorial times due to their health beneficial properties. It is known that functional properties of Allium genus come from the high content of bioactive compounds. The biological activity of Allium extracts will be conditioned by the type of Allium variety, agricultural conditions, and specific extraction process used since all these factors affect the content and the profile of bioactive compounds. Innovative extraction techniques in comparison to conventional processes could be considered as a promising tool to recover bioactive compounds from Allium spp. with antimicrobial and anti-inflammatory properties. Trying to fill the gap in the literature, this paper reviews the chemical composition, the effects of processing on the nutritional and bioactive composition of Allium species and their extracts. Moreover, the antimicrobial and anti-inflammatory effects, as well as the bioavailability of bioactive compounds of edible members from the Allium genus is discussed.